Pendeteksian Kecurangan Pelaporan Keuangan Menggunakan Fraud Pentagon - Anggun Anindita Ghaisani; Supatmi Supatmi (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the effect of the pentagon fraud on financial statement fraud. The factors in the fraud pentagon consist of five elements, namely pressure is proxied by financial targets, opportunity is proxied by ineffective monitoring, rationalization is proxied by change in auditors, capability is proxied by change of directors, and arrogance is proxied by frequents number of CEO's pictures. This study uses the F-Score Model to detect the potential for fraudulent financial statements.This type of research is descriptive quantitative. The data source used is secondary data, namely the company's annual report obtained through the Indonesia Stock Exchange website (www.idx.co.id) and the company's official website as the sample. The population of this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. Sample selection using purposive sampling method. The total sample obtained is 20 companies with 5 years of observation, so that obtained 100 observation data. The data analysis technique used is a panel data regression model which is processed using Eviews 10. The results show that the financial target, ineffective monitoring and change of director variables have a positive effect on financial statement fraud. Meanwhile, the change in auditor and frequent number of CEO's picture variables have no effect against fraudulent financial statements.